DETERMINATION OF BATTERY WASTE MANAGEMENT STRATEGY IN THE IMPLEMENTATION OF ELECTRIC MOTORCYCLES IN DENPASAR CITY - Otniel Stefen Adi Prasetyo; Qomariatus Sholihah; Takahiro Osawa; Ni Made Pertiwi Jaya; I Made Dwi Arbani (Universitas Trisakti, 2023)
Electric two-wheelers are becoming increasingly popular in Indonesia, particularly in the city of Denpasar; due to government regulations and social action, programs growing the number of electric motorcycles will impact the generation of toxic and hazardous waste in the form of used batteries which can cause environmental pollution if not managed properly. In connection with the establishment of a lifecycle-based business ecosystem and reduction of pollution risks, the thing that needs serious attention is the development of independent battery waste management facilities in Denpasar City. Aim: In this regard, a study was conducted on the development and management strategy of used battery waste for electric motorcycles in Denpasar City. Methodology and Results: Data was analyzed on primary data collected through in-depth interviews with key persons and questionnaires and secondary data obtained from related institutions. The development strategy was directed at six indicators, i.e., economy, interest, infrastructure, media, technology, and battery waste management facilities. By considering the six strategy indicators, the location of battery waste management facilities from four sub-districts in Denpasar City was determined using the Analytic Hierarchy Process (AHP) method, where the South Denpasar Sub-district was obtained as the top priority with a value of 0.403. Conclusion, significance, and impact study: This strategy is expected to be a direction for implementing electric motorcycle vehicles in Denpasar City